Cervical dystonia: an update on therapeutics. (3rd April 2019) - Mittal, Shivam Om; Lenka, Abhishek; Jankovic, Joseph
ABSTRACT: Introduction : Cervical dystonia is the most common focal dystonia encountered in a movement disorders clinic. It may have a huge impact on patients' quality of life due to involuntary movement and abnormal posture of the head, neck pain, limitations in the range of neck movements, and psycho-social stress. Botulinum toxin is the preferred treatment due to its efficacy and favorable safety profile. In addition to anticholinergics and muscle relaxants, deep brain stimulation and peripheral denervation surgeries are also available but should be considered only in otherwise refractory patients. Areas covered : This article focuses on the current understanding and advances in the therapeutics for cervical dystonia. The authors have comprehensively reviewed the literature on various treatment options including physiotherapy, oral medications, botulinum toxin injections, and surgical interventions. Expert opinion : Several treatment options are available for patients with cervical dystonia. In mild cases, physiotherapy and muscles relaxants may be satisfactory, but botulinum toxin remains the mainstay of treatment for most. Over the past three decades since the introduction of botulinum toxin for therapeutic use, there is a better understanding of the efficacy and safety of botulinum toxin formulations. Despite advances, there are knowledge gaps that need to be addressed in future studies.